GLOBALISASI MEMPERKUAT KEARIFAN LOKAL - Komang Trisna Mahartini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Globalization must be interpreted according to the local thinking of the Indonesian people. All problems that arise from globalization, must be accessible based on the local wisdom of the local community. Global problem solving is focused on two fields in the field of education as software and culture as hardware that will form local people who can solve problems that arise globalization locally. Hope that can be made by Indonesians who are global in mind but act locally. The next step of the learning process is a comprehensive activity (physical and mental) that is carried out gradually and continuously to develop knowledge and skills. These activities emphasize human abilities, namely the ability to move, talk, and the ability to think. In addition, the more turbulent in choosing globalization, the stronger the local wisdom of the Indonesian people to be preserved. Thus, there is globalization that can be approved by local wisdom of the Indonesian people.